Hydrogenated nanotubes/nanowires assembled from TiO2 nanoflakes with exposed 111 facets: excellent photo-catalytic CO2 reduction activity and charge separation mechanism between (111) and (1̄1̄1̄) polar surfaces. Issue 24 (5th June 2019) - Liu, Junfang; Liu, Bin; Ren, Yan; Yuan, Yukun; Zhao, Hua; Yang, Heqing; Liu, Shengzhong (Frank)
Abstract : The apparent quantum yield for CH4 evolution of the hydrogenated TiO2 nanotubes/nanowires is as high as 17.4%, which is higher than that of all the TiO2 based photocatalysts reported until now. Abstract : Nanotubes/nanowires assembled from TiO2 nanoflakes with exposed 111 facets were prepared via heating a mixture of titanium(iv ) oxysulfate–sulfuric acid hydrate, glacial acetic acid and water. The photocatalytic CO2 reduction activity of the as-prepared TiO2 nanoflake based nanotubes/nanowires was remarkably increased through hydrogenation. The apparent quantum yield for CH4 evolution of the hydrogenated TiO2 nanotubes/nanowires is as high as 17.4%, which is higher than that of all the TiO2 based photocatalysts reported until now. The excellent photocatalytic performance is ascribed to the exposed clean TiO2 111 facets and enhanced solar absorption. On the basis of the polar structure of the exposed TiO2 111 crystal facets, we proposed a separation mechanism of photocreated electrons and holes. A spontaneous electric field (Es) is created between polar TiO2 (111) and (1̄1̄1̄) planes. Under Es, the photocreated electrons and holes transit to TiO2 (111) and (1̄1̄1̄) surfaces, respectively. Redox reactions selectively take place at the Ti–TiO2 (111) and O–TiO2 (1̄1̄1̄) polar planes. The charge separation mechanism provides a clear insight for understanding the photocatalysis of high performance semiconductor nanocrystals and offers guidance for the design of high performance photocatalysts for CO2 reduction.